Assessment of the quality of life of pediatric patients at a center of excellence in dermatology in southern Brazil Avaliação da qualidade de vida dos pacientes pediátricos de um centro de referência em dermatologia no sul do Brasil - Magda Blessmann Weber; Daniel Lorenzini; Clarissa Prieto Herman Reinehr; Bárbara Lovato (Sociedade Brasileira de Dermatologia, 2012)
BACKGROUND: Skin diseases cause negative impact on the emotional state, social relationships and daily activities, due to the stigma caused by the appearance of the lesions. OBJECTIVE: This study aimed to assess the quality of life of pediatric patients with skin diseases attending a dermatology service, compare the scores obtained among the dermatoses found in the sample and associate them to the variables, in addition to observing how the skin disease specifically affects quality of life. METHODS: Cross-sectional study, with patients between 5 and 16 years attending the Dermatology Service of the University of Health Sciences of Porto Alegre, Brazil, between July 2010 and February 2011. The data collection instruments were the Children's Dermatology Life Quality Index questionnaire and the AUEQI questionnaire. RESULTS: A total of 161 patients were interviewed, with mean age of 9,66 years. The main dermatoses were atopic dermatitis (29.8%), warts (13%) and molluscum contagiosum (7.5%). Chronic diseases (73.9%) were the most prevalent. The overall mean Children's Dermatology Life Quality Index score was 5.01 for chronic dermatoses and 2.07 for acute illnesses, indicating a compromised quality of life among chronically ill patients. The comparison between the scores obtained with the AUEQI scale and the Children's Dermatology Life Quality Index scores indicates that the overall quality of life is less affected than the specific quality of life related to the dermatosis. CONCLUSIONS: The data presented reinforce how important it is that the patients, their families and caregivers understand the symptoms, triggers and treatment of the skin disease in question. This information facilitates adherence to the treatment and justifies the conduct adopted by the dermatologist. FUNDAMENTOS: Doenças dermatológicas, em razão dos estigmas pela aparência das lesões, são fonte de impacto negativo no estado emocional, relações sociais e atividades cotidianas. OBJETIVOS: Este estudo objetiva avaliar a qualidade de vida nos pacientes dermatológicos pediátricos em um centro de referência em dermatologia, comparar os índices de qualidade de vida entre as dermatoses e associá-los às variáveis, além de avaliar de que forma as dermatoses afetam a qualidade de vida especificamente. MÉTODOS: Estudo analítico transversal, pacientes entre 5 e 16 anos, do Serviço de Dermatologia da Universidade Federal de Ciências da Saúde de Porto Alegre, entre julho de 2010 e fevereiro de 2011. Instrumentos utilizados: questionário Índice Pediátrico de Qualidade de Vida em Dermatologia e escala AUQEI. RESULTADOS: Um total de 161 pacientes, média de idade de 9,66 anos. As principais dermatoses foram dermatite atópica (29,8%), verrugas vulgares (13%) e molusco contagioso (7,5%). Doenças crônicas (73,9%) foram mais prevalentes. A média do Índice Pediátrico de Qualidade de Vida em Dermatologia de 5,01 para dermatoses crônicas, e de 2,07 em agudas, indicando maior comprometimento da qualidade de vida entre os pacientes cronicamente enfermos. A comparação entre os escores obtivos com a escala AUEQI e o Índice Pediátrico de Qualidade de Vida em Dermatologia indicam que a qualidade de vida global é afetada com menor intensidade do que a relacionada especificamente à dermatose. CONCLUSÃO: Os dados obtidos reforçam a importância do entendimento dos sintomas, desencadeantes e da terapêutica da dermatose em questão pelos pacientes, por seus familiares e por seus cuidadores. Tais infomações facilitam a aderência ao tratamento e justificam a conduta adotada pelo dermatologista.